Gambling Debt Iceland's Rise and Fall in the Global Economy - Durrenberger, E. Paul; Palsson, Gisli (University Press of Colorado, 2014)
Gambling Debt is a game-changing contribution to the discussion of economic crises and neoliberal financial systems and strategies. Iceland's 2008 financial collapse was the first case in a series of meltdowns, a warning of danger in the global order. This full-scale anthropology of financialization and the economic crisis broadly discusses this momentous bubble and burst and places it in theoretical, anthropological, and global historical context through descriptions of the complex developments leading to it and the larger social and cultural implications and consequences.